Pengetahuan Remaja Putri Tentang Kesehatan Organ Genetalia Eksterna di SMA Negeri 4 Kota Padangsidimpuan - Siregar, Nurelilasari; Pebrianthy, Lola (Universitas Aufa Royhan, 2019)
According to WHO (World Health Organization) in research women rarely pay attention to their own genitals, especially in a state of menstruation and if not cleaned will result in vaginal infections. Infection in the vagina each year attacks infections in women around the world 10-25% of 100 million women. In Indonesia, the reproductive organs get less attention in daily life, this is caused by our culture which sometimes feels uncomfortable to talk about sexual problems. objective: To determine the description of knowledge of young women about the health of external genetal organs. Method: This study uses a descriptive design with a cross-sectional approach. Sampling was done by random sampling technique, as many as 56 people. Data analysis was performed descriptively. Results: The knowledge of adolescent girls about the health of external genetal organs the majority of respondents lack knowledge as many as 24 respondents (42.9%). Conclusion: this study proves that there is still a lack of adolescent knowledge related to the health of external genetal organs.